Determinants of Audit Report Lag during the Covid-19 Pandemic: A Study on Companies Conducting IPOs and Indexed LQ-45 - Yanti Yanti; Bayu Pasupati; T. Husain (Universitas Pendidikan Ganesha, 2022)
This research will re-examine the factors that influence the audit report lag, including profitability, size of public accounting firms, and firms' age at companies conducting IPOs in 2019 and including the LQ-45 index on the Indonesia Stock Exchange during the COVID-19 pandemic. This study uses the Big-Four categorization as a proxy of size of the public accounting firm. This type of research uses the causal effect with a quantitative research approach. The final sample was determined to be 99 company data. The data analysis technique used multiple regressions. The results showed that the audit report lag was negatively influenced by the size of public accounting firms and firms' age, while the profitability factor did not affect it. The audit report lag contribution was influenced by the three factors above and simultaneously.